Importance of Old and Local Apple Cultivars - Szot, Iwona; Goncharovska, Inna; Klymenko, Svitlana; Bulakh, Petro (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2022)
Apples are among the most consumed fruits in the world. After China, the European Union is one of the biggest producers of apples. Due to the appropriate soil and climatic conditions, Poland is a leading producer of these fruits in the world and the European Union. Currently, the cultivar structure on the European market is limited to about 12 varieties. This leads to the genetic impoverishment and loss of many local cultivars. Due to the unattractive external appearance of apples or the alternation of fruiting, are losing to the currently popular standards. The breeding of new cultivars is based on a limited number of ancestors, which poses the risk of reduced genetic diversity. The decline in biodiversity is also due to crop specialization. In every region of the world where apple cultivation has developed, there are many cultivars of unknown origin, which are referred to as local cultivars. They often have unique nutritional values or traits that enable them to survive. The preservation of these cultivars is justified due to the possibility of their use in breeding new cultivars, including those resistant to diseases. They can also be used in the food industry for the production of juices, cider, and high-percentage distillates, as well as functional food. In addition, due to the higher content of some health-promoting ingredients, they are suitable for the production of, for example, anti-ageing cosmetics. There are few native old cultivars in Poland. Before World War II, apple trees of English, French, German, Italian, Dutch, Belgian, Czech, Russian, and American origin predominated in Polish orchards. Old and local cultivars have remained only in home orchards, but due to the relatively short life of apple trees, they are in danger of becoming extinct. Poland protected old and local cultivars by ratifying the Convention on Biological Diversity of Rio de Janeiro in 1992. The collection and preservation of these apple cultivars are carried out by research centres and Botanical Gardens, among others in Warsaw, Poznań, Bolestraszyce, Drawa, and Lublin.